Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Anwar Hakim Md Rozhdi - Md Rozhdi, Anwar Hakim (2021)
Sony is a company that strives to be the best. Our corporate strategy is to market and market creative and high-quality electronic consumer goods. As part of the company’s ongoing mission to consistently provide the industry's best dealer support, Sony Malaysia is launching its new Sony Designated Store Program to help distributors provide a better level of visual merchandising and customer services, while at the same time reducing distributor costs. One of products that produce by this company is headphones. The product has headband, in-ear and wireless headphone. The purpose of this case study is to identify, analyse and investigate the company-based product, the problems of the product and proposed solutions to solve the problems. In this case study I will focus on in-ear headphone. After doing the product analyses the latest Sony IER-Z1R Signature Series In-ear Headphones does not meet the tastes of customers. The problems are this headphone’s price are very expensive but not suitable for sports event. Next, it also not suitable during extreme weather and this headphone does not support for video gaming. This study come out the best solution in the problem. The best solution is making an innovation for wide angle front camera by making a small lens device. In this situation, there are two types of users that are not interested in front angle and like wide angle. This is because, the wide-angle front camera also plays an important role in seeing the wide front situation.